Cellular Uptake: Uptake Kinetics and Nanotoxicity of Silica Nanoparticles Are Cell Type Dependent (Small 23/2013). Issue 23 (9th December 2013) - Blechinger, Julia; Bauer, Alexander T.; Torrano, Adriano A.; Gorzelanny, Christian; Bräuchle, Christoph; Schneider, Stefan W.
<x xml:space="preserve">Abstract</x> Three‐dimensional atomic force microscopy is combined with fluorescence microscopy to investigate the cellular uptake of silica nanoparticles into human cells. As reported on page 3970 by C. Bräuchle, S. W. Schneider, and co‐workers, nanoparticles (red dots in the image) are visible on the plasma membrane outside of the cells. Interestingly, after longer exposure times, the surface of the cells may also be characterized by homogeneous distribution of small humps, indicating intracellular localization of nanoparticles. Results obtained using this technique confirm that the cellular response to silica nanoparticles is cell type dependent. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>